Autocatalytic synthesis of multifunctional precursors for fabricating silica microspheres with well-dispersed Ag and Co3O4 nanoparticles. Issue 2 (21st December 2016) - Xu, Linxu; Cui, Fang; Zhang, Jiajia; Hao, Yanjun; Wang, Yan; Cui, Tieyu
Abstract : Silica spheres with small-sized and well-dispersed Ag and Co3 O4 NPs were synthesized through spontaneous autocatalytic routes by using a designed multifunctional sol–gel precursor. Abstract : Herein, an autocatalytic route to fabricate dual metal ion-equipped organic/inorganic hybrid silica, an ideal precursor for multifunctional silica-based composites integrated with well-dispersed Ag and Co3 O4 nanoparticles was demonstrated. Significantly, by rational selection of reactants, such dual metal ion-equipped organic/inorganic hybrid silica can be synthesized through successive spontaneous reactions under near neutral conditions without an additional catalyst. Both the Ag + and Co 2+ ions are introduced into silica by chemical bonds, which favor the formation of small-sized and well-dispersed Ag and Co3 O4 nanoparticles without aggregation in the entire silica matrix. After calcination, multifunctional silica composites equipped with well-dispersed Ag and Co3 O4 nanoparticles were obtained. The as-obtained silica composites, as indicated by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), have a spherical morphology and smooth surface. TEM tests also reveal the well dispersed fashion of Ag and Co3 O4 nanoparticles. In addition, the obtained Ag–Co3 O4 @SiO2 composites exhibit good catalytic performance in the reduction of methylene blue (MB) with NaBH4 as a reducing agent, and can be readily recycled by an external magnetic field due to their superparamagnetic properties.